PERANCANGAN TATA LETAK DEPARTEMEN FINISHING PABRIK CV. SG-BANDUNG - Nita Puspita Anugrawati Hidayat (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
CV. SG Bandung is a convection company that produces moslem clothes. High competitive in market push company to be more effective and efficient.Company must be able to increase productivity on the production floor and reduce cost.From this observation, CV. SG doesn’t have a good layout. It seen from the departments and facilities in finishing department placement that have not been arranged properly. One of the parameters of a good layout is minimize material handling cost which can be seen from the movement moment, which is calculated by multiplying the distance and frequency of material movement between facilities. Before preparing the new layout, it needs the initial layout, from-to chart, move-cost chart which becomes input for CRAFT algorithm in the WinQSB software.Through this research, can be obtained the plant facility layout design is better, it can be seen from the movement moment which can be reduced in the finishing department proposed layout.